Socio-political factors underlying the adoption of green bond financing of infrastructure projects: The case of Ghana - Prosper Babon-Ayeng; Eric Oduro-Ofori; De-Graft Owusu-Manu; David James Edwards; Ernest Kissi; Augustine Senanu Komla Kukah (Journal of Capital Markets Studies (JCMS), 2022)
Purpose: There is a pressing need to increase investments in sustainable infrastructure to promote low carbon economic growth and ensure environmental sustainability. Consequently, this study examines the socio-political factors underlying the adoption of green bond financing of infrastructure projects. Design/methodology/approach: Primary data was gathered from experts with advanced experience in, or knowledge of green bonds in the Kumasi Metropolis. To identify respondents with pertinent knowledge that is relevant to the study, purposive and snowball sampling techniques were used. One-sample t-test and relative importance index were used in this study's statistical analysis. Findings: "Training and experience with sustainable finance" was seen as the most important social factor underlying the adoption of green bond financing of infrastructure projects by the respondents and 'Governmental tax-based incentives' was rated as the leading political factor. Originality/value: This pioneering research attempts to ascertain the socio-political factors affecting the adoption of green bond financing of infrastructure projects. Emergent results of analysis and concomitant discussions add knowledge to fill a void in literature on the social and political factors affecting the adoption of green bond financing of infrastructure projects in developing countries.
Keywords: 330; Socio-political; Green bond; Infrastructure; Sustainable finance; Ghana